Developing Electronic English Educational Cartoon (E-EduToon): A Culturally-Based Supplementary Material for Reading Instruction - Akhris Fuadatis Sholihah; Adhan Kholis (Journal of General Education and Humanities, 2025)
This research aimed to develop an interactive e-book integrating traditional games, such as Cublak-Cublak Suwung and Truth or Dare cards, with structured scaffolding to support English language learning. The researchers implemented scaffolding through step-by-step exercises that progressively guided students in understanding texts. While many studies have explored digital media in language learning, research on interactive e-books incorporating traditional games and scaffolding remains limited. Addressing this gap, this study employed a Research and Development (R&D) approach consisting of analysis, design, development, implementation, and evaluation. Using a mixed-methods design, quantitative data from 15 seventh-grade students was collected through Likert-scale questionnaires, and qualitative data was collected from interviews with an English teacher, observations, and student questionnaires. The e-book was validated by two experts in design and content, with validation scores of 4.33 from the media expert and 4.23 from the content expert, while students rated it 4.22, confirming its high validity. Additionally, student feedback indicated a strong interest in using the e-book for English learning, with an average score of 4.35. This innovative approach supports more engaging, culturally relevant English learning, making it a valuable resource for classrooms and supplementary learning, particularly among Indonesian learners.